The Effect of Age-related Differences in Body Size and Composition on Cardiovascular Determinants of VO(2)max - Carrick-Ranson, Graeme (Oxford University Press, 2013)
BACKGROUND. A reduction in maximal stroke volume (SV(max)) and total blood volume (TBV) has been hypothesized to contribute to the decline in maximal oxygen uptake (VO(2)max) with healthy aging. However, these variables have rarely been collected simultaneously in a board age range to support or refute this hypothesis. It is also unclear to what extent scaling size-related cardiovascular determinants of VO(2)max affects the interpretation of age-related differences. METHODS. A retrospective analysis of VO(2)max, maximal cardiac output (Q(C)max), TBV, and body composition including fat-free mass (FFM) in 95 (51% M) healthy adults ranging from 19–86 years. RESULTS. Absolute and indexed VO(2)max, Q(C)max, and maximal heart rate decreased in both sexes with age (p ≤ .031). SV(max) declined with age when scaled to total body mass or body surface area (p ≤ .047) but not when expressed in absolute levels (p = .120) or relative to FFM (p = .464). Absolute and indexed TBVs (mL/kg; mL/m(2)) were not significantly affected by age but increased with age in both sexes when scaled to FFM (p ≤ .013). A lower arteriovenous oxygen difference (a-vO(2)diff) contributed to the reduction in VO(2)max with age in treadmill exercisers (p = .004) but not in the entire cohort (p = .128). CONCLUSION. These results suggest (a) a reduction in absolute SV(max), and TBV do not contribute substantially to the age-related reduction in VO(2)max, which instead results from a smaller Q(C)max due to a lower maximal heart rate, and (b) body composition scaling methods should be used to accurately describe the effect of aging on physical function and cardiovascular variables.